EXPERIENCE OF THE ORGANIZATION OF VIRTUAL LABORATORIES ON THE BASIS OF TECHNOLOGIES OF CLOUD COMPUTING - V. Oleksyuk (Kherson State University, 2014)
The article investigated the concept of «virtual laboratory». This paper describes models of deploying of cloud technologies in IT infrastructure. The hybrid model is most recent for higher educational institution. The author suggests private cloud platforms to deploying the virtual laboratory. This paper describes the experience of the deployment enterprise cloud in IT infrastructure of Department of Physics and Mathematics of Ternopil V. Hnatyuk National Pedagogical University. The object of the research are virtual laboratories as components of IT infrastructure of higher education. The subject of the research are clouds as base of deployment of the virtual laboratories. Conclusions. The use of cloud technologies in the development virtual laboratories of the is an actual and need of the development. The hybrid model is the most appropriate in the deployment of cloud infrastructure of higher educational institution. It is reasonable to use the private (Cloudstack, Eucalyptus, OpenStack) cloud platform in the universities.